Phosphorus mobilization and delivery estimated from long-term high frequency water quality and discharge data - Mellander, Per-Erik; Galloway, Jason; Hawtree, Daniel; Jordan, Phil (Frontiers in Water, 2022)
Efficient and targeted measures to mitigate nutrient losses to water are required to meet the challenges of increased food production and climate change. Diffuse pollution management requires insight into the underlying processes of nutrient transfer and its stability, but there are no standardized ways to evaluate phosphorus (P) mobilization and delivery at the catchments scale. Here we suggest a method that allows to systematically and objectively describe catchment scale processes of P transfer to water. Ten years of sub-hourly P concentration and hydrometric data from six agricultural catchments, with different physical characteristics, were assessed to introduce a method for estimation of a P mobilization index and a P delivery index. The former was defined as P detachment/solubilization expressed as ratios of P concentration percentiles, and the latter as connectivity/retention expressed as ratios of P mass load percentiles. Estimating these indices over several years provided insights on the stability of transfer processes over time and the identification of inter-annual trends. The indices were also used to quantify components of the P transfer continuum. This was used as a screening tool to compare and classify catchment specific and potential P loss risks. While the groundwater driven catchments had a higher P mobilization index for reactive P, the hydrologically flashy catchments had higher delivery indices for total P and particulate P + organic P. Increasing or decreasing inter-annual trends were mostly found in catchments with a chemo-dynamic response in the discharge-concentration relationship. In three catchments the environmental quality standards were frequently exceeded caused by different risks and the P loss screening tool identified the type of risk. Development of the P mobilization and delivery indices was possible with long-term and high frequency monitoring of water quality and discharge from catchments of different typologies, together with a conceptual understanding of the catchments. More catchments of different typologies, management, scales and from different climatic zones are needed for further development of the indices.